Voltammetric Detection of Uric Acid at Screen Printed Electrode: A Review - Wulan Tri Wahyuni; Dyah Iswantini Pradono; Selvitia Ulandari (Hasanuddin University, 2021)
Uric acid is a compound produced from purine metabolism. The excess amount of these compounds could causes diseases in the body. Effective and practical methods are needed for early detection of uric acid. Technically, uric acid could be detected using enzymes (enzymatic) and without enzymes (non-enzymatic). Several methods have already reported for uric acid detection in biological samples, including fluorimetry, colorimetry, liquid chromatography, flow injection analysis, chemiluninescence, and electrochemical detection. Among electrochemical detection methods, voltammetry is one of the most prospective for uric acid detection. This review covers the approach of uric acid detection including enzymatic and nonenzymatic approach, several voltametric technique for uric acid detection, and screen printed and modified electrode as platform for uric acid detection. Analytical performance such as linear range, sensitivity, selectivity and reproducibility of uric acid detection using various voltametric method and at different platform were also highlighted.